STILISTIKA NILAI EDUKATIF QUOTE KHR. AHMAD AZAIM IBRAHIMY - Yulia Tutik Nurfia; Miftahul Alimin (LP2M Universitas Ibrahimy, 2021)
This research is based on the style used by KHR. Ahmad Azaim Ibrahimy through his snippet of da'wah (quote) that has interesting style of languages, education messages delivered simply but so attractive. The aim of this research was to analyze and to study the language style of quotes used by KHR. Ahmad Azaim Ibrahimy in religion speech and the implementation in running his function in Pondok Pesantren Syalafi’iyah-Syafi’iyah. The research approach used was descriptive qualitative that focused on analytics and didactics. Data collection method had used the textual data analysis in language style of KHR. Ahmad Azaim Ibrahimy. The research result showed that in language style of KHR. Ahmad Azaim Ibrahimy there were metaphor, personification, allegory, irony, association, simile, metonymies, euphemism, and pleonasm figures of speech. The messages of the quotes can be understood by the readers, especially the students and the alumni of Pondok Pesantren Syalafi’iyah-Syafi’iyah.